Proteomic analysis of three Borrelia burgdorferi sensu lato native species and disseminating clones: Relevance for Lyme vaccine design. Issue 7 (4th February 2015) - Schnell, Gilles; Boeuf, Amandine; Jaulhac, Benoît; Boulanger, Nathalie; Collin, Elody; Barthel, Cathy; De Martino, Sylvie; Ehret‐Sabatier, Laurence
<x xml:space="preserve">Abstract</x> Lyme borreliosis is the most important vector‐borne disease in the Northern hemisphere. It is caused by Borrelia burgdorferi sensu lato bacteria transmitted to humans by the bite of hard ticks, Ixodes spp. Although antibiotic treatments are efficient in the early stage of the infection, a significant number of patients develop disseminated manifestations (articular, neurological, and cutaneous) due to unnoticed or absence of erythema migrans, or to inappropriate treatment. Vaccine could be an efficient approach to decrease Lyme disease incidence. We have developed a proteomic approach based on a one dimensional gel electrophoresis followed by LC‐MS/MS strategy to identify new vaccine candidates. We analyzed a disseminating clone and the associated wild‐type strain for each major pathogenic Borrelia species: B. burgdorferi sensu stricto, B. garinii, and B. afzelii. We identified specific proteins and common proteins to the disseminating clones of the three main species. In parallel, we used a spectral counting strategy to identify upregulated proteins common to the clones. Finally, 40 proteins were found that could potentially be involved in bacterial virulence and of interest in the development of a new vaccine. We selected the three proteins specifically detected in the disseminating clones of the three Borrelia species and checked by RT‐PCR whether they are expressed in mouse skin upon B. burgdorferi ss inoculation. Interestingly, BB0566 appears as a potential vaccine candidate. All MS data have been deposited in the ProteomeXchange with identifier PXD000876 (http://proteomecentral.proteomexchange.org/dataset/PXD000876).